2021
DOI: 10.1021/acsami.1c19447
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Cartilage ECM Enhances the Chondrogenesis of Endogenous Cells and Subchondral Bone Repair of the Unidirectional Collagen–dECM Scaffolds in Combination with Microfracture

Abstract: Despite the formation of mechanically inferior fibrocartilage, microfracture (MF) still remains the gold standard to repair the articular cartilage defects in clinical settings. To date, although many tissue-engineering scaffolds have been developed to enhance the MF outcome, the clinical outcomes remain inconsistent. Decellularized extracellular matrix (dECM) is among the most promising scaffold for cartilage repair due to its inheritance of the natural cartilage components. However, the impact of dECM from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…51 There were agglomerations of BMSCs, which favored chondrogenesis. 52 Furthermore, the calculation results showed that cells in the Col-Apt@KGN MPs hydrogel and Col@KGN MPs hydrogel were relatively round, and their spreading area was relatively small on Day 7 (Fig. 4D and E).…”
Section: Resultsmentioning
confidence: 90%
“…51 There were agglomerations of BMSCs, which favored chondrogenesis. 52 Furthermore, the calculation results showed that cells in the Col-Apt@KGN MPs hydrogel and Col@KGN MPs hydrogel were relatively round, and their spreading area was relatively small on Day 7 (Fig. 4D and E).…”
Section: Resultsmentioning
confidence: 90%
“…Among them, childhood cartilage is considered the optimal ECM source for the further development of ECM-based tissue engineering scaffolds in AC repair. 142 In addition, ECM from different cartilage types has specific functions in inducing stem cells to osteogenesis or chondrogenic differentiation due to their different bioactive factors. Mass spectrometry revealed that the growth plate and AC ECM contain a unique array of regulatory proteins.…”
Section: Articulate Cartilage Defects Therapeutic Strategiesmentioning
confidence: 99%
“…Decellularized extracellular matrix (dECM) refers to biological materials formed by human or animal tissues or organs through decellularized methods [ 40 ]. Decellularized muscle matrix biomaterials were first reported in 1948; scientists have gradually deepened their research correlated with dECM in recent years [ 41 , 42 , 43 , 44 , 45 ]. Some dECM materials are FDA-approved, such as AlloDerm ® for skin repair [ 46 ].…”
Section: Strategiesmentioning
confidence: 99%